EXPLORATORY STUDY OF WORKPLACE BULLYING TOWARDS EMPLOYEE PERFORMANCE, JOB STRESS, AND EMPLOYEE LOYALTY AT PT. PLN (PERSERO) AREA MANADO - Hutadjulu, Rebecca R. P; Saerang, David P. E.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Workplace bullying is every negative behaviour/practice that is done intentionally or accidentally towards an individual or more in the working environment. This particular phenomenon poses as a major human resource problem that has great impact towards the employees. Receiving constant negative behaviours cannot be good for a person as it has the potential to harm their physical safety and mental well-being. This research uses the qualitative method in order to explore the workplace bullying by discovering the motives behind it. Furthermore, this research will help the readers to understand the consequences of workplace bullying toward the employees and the organisation itself. This research found that bullying does happen in the organisation, however Perceived Organisational Support (POS) plays a crucial part in retaining the employees. The research highlights the employees’ lack of awareness about workplace bullying and how disadvantageous it is because they might have been the victim without knowing it. The organisation must consider establishing a training program about bullying practices in the workplace in order to introduce the concept and increase employees’ awareness of it. Furthermore, creating a policy to ensure its legality might be the best precaution method against it. Keywords: workplace bullying, job stress, employees’ performance, employee loyalty